2016
DOI: 10.1152/ajpheart.00075.2015
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in intraventricular kinetic energy: a physiological or pathological adaptation?

Abstract: Measuring intracardiac kinetic energy using four-dimensionl flow cardiac magnetic resonance provides important information on the decline in the early diastolic kinetic energy of blood with aging. The decline is comparable with that seen in those with heart failure and may be a marker of cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
5
28
0
Order By: Relevance
“…This increase in residual volume is consistent with the decreased through-plane flow in the apex (since residual flow pathlines are typically located in or near the apex) and with the notion of increased stasis post MI. Our control data have similar flow rates to those reported in 1995 [21] and similar KE values to those reported in 2015 [22] and 2016 [23] in healthy controls. Our control data however displays a greater fraction of flow in the direct flow compartment and less in the residual volume compartment than Eriksson et al found in 2010 [19] and 2013 [24].…”
Section: Discussionsupporting
confidence: 90%
“…This increase in residual volume is consistent with the decreased through-plane flow in the apex (since residual flow pathlines are typically located in or near the apex) and with the notion of increased stasis post MI. Our control data have similar flow rates to those reported in 1995 [21] and similar KE values to those reported in 2015 [22] and 2016 [23] in healthy controls. Our control data however displays a greater fraction of flow in the direct flow compartment and less in the residual volume compartment than Eriksson et al found in 2010 [19] and 2013 [24].…”
Section: Discussionsupporting
confidence: 90%
“…Since these measures reflect the hemodynamics of the entire LV, and we found that the flow in the LV apex was most acutely affected in our anterior AMI cohort, it follows that the global KE measures would be less sensitive to post-MI flow changes in this cohort than regional flow measures in the apex. Our control data have similar flow rates to those reported in 1995 [20] and similar KE values to those reported in 2015 [21] and 2016 [22] in healthy controls. Peak systolic flow in the LV base was negatively correlated with heart rate and circumferential strain and positively correlated with stroke volume and ejection fraction.…”
Section: Discussionsupporting
confidence: 90%
“…Research by Wong et al . supports the finding that peak E-wave LV blood flow KE declines with age 19 , despite differences in study design to the present study. The current study is the first to compare 4D blood flow LV energetics with existing 2D standard mitral inflow metrics of diastolic function for their association to advancing age.…”
Section: Discussionsupporting
confidence: 89%